2022
DOI: 10.1097/pxr.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of foot-toe orthoses on three-dimensional pelvic kinematics in individuals with hallux valgus during gait

Abstract: Background: Most previous studies focused on the possible relationship between hallux valgus deformity and biomechanical characteristics in the foot and lower leg. Very few investigated the association of pelvic kinematics and hallux valgus during gait according to various foot-toe orthoses for hallux valgus. Objective: To investigate the effect of soft or hard foot-toe orthoses on pelvic kinematics in individuals with hallux valgus deformity during gait.Study design: This study has a repeated measures design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…For example, a previous study reported that pelvic motion during walking improved after wearing orthoses in HV patients. 23 Second, we obtained a foot model in a non-weight-bearing condition. Under weight-bearing, there may be a mismatch between the orthosis and the foot, resulting in distortion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study reported that pelvic motion during walking improved after wearing orthoses in HV patients. 23 Second, we obtained a foot model in a non-weight-bearing condition. Under weight-bearing, there may be a mismatch between the orthosis and the foot, resulting in distortion.…”
Section: Discussionmentioning
confidence: 99%